Experimental investigation of water-saving efficiency using hexagonal diamond-shaped floating covers in large-scale evaporation ponds under static water conditions - ZongLe Duan; KeBin Shi; KeWu Han; Tayi Abudula (PLoS ONE, 2026)
To investigate the evaporation suppression and water conservation effects of hexagonal diamond-shaped floating covers (HDFCs) under static water conditions, this study conducted experiments in circular evaporation ponds during the non-freezing period of 2024 (March 19 to November 30). The floating covers were arranged edge-to-edge and corner-to-corner, and daily water level observations were recorded. The evaporation reduction rate was calculated using the weighted average method. The results showed that with a porosity of 17.28%, the floating cover reduced evaporation by 1505.21 mm during the non-freezing period, corresponding to a water conservation rate of 74.86% relative to the total evaporation from the natural water surface (2010.7 mm). Theoretical analysis further indicated that if the floating covers fit perfectly with the pond edges, achieving a coverage rate of 98%, the theoretical water conservation rate could reach 88.59% based on the linear proportional scaling assumption. To validate practical applicability, supplementary experiments were conducted in a dynamic water environment (an unshielded large pond with natural wind and waves). The results demonstrated that the evaporation suppression rate remained above 70%, which is comparable to the results under static water conditions. This study confirms that hexagonal diamond-shaped floating covers exhibit effective evaporation suppression and water conservation performance under static water conditions and hold potential for practical application in open water bodies such as reservoirs.